Superiorization of incremental optimization algorithms for statistical tomographic image reconstruction - Helou, E. S. [UNESP]; Zibetti, M. V. W.; Miqueles, E. X. (Iop Publishing Ltd, 2017)
We propose the superiorization of incremental algorithms for tomographic image reconstruction. The resulting methods follow a better path in its way to finding the optimal solution for the maximum likelihood problem in the sense that they are closer to the Pareto optimal curve than the non-superiorized techniques. A new scaled gradient iteration is proposed and three super-iorization schemes are evaluated. Theoretical analysis of the methods as well as computational experiments with both synthetic and real data are provided.
Keywords: superiorization; convex optimization; tomographic image reconstruction